Impact and Mechanistic Insights of Low-Sodium Salt and Magnesium-Enriched Compound Seasoning on Blood Pressure in Rats - HE Xiong, YOU Enzhuo, LI Jiaxing, XU Huanhuan, YUE Yuanyuan, ZHANG Yingshuai (Shipin Kexue, 2025)
This research aims to explore the difference between low-sodium salt and magnesium-containing compound seasonings in maintaining healthy blood pressure levels. A comparative study was conducted through a short-term animal feeding experiment, and the underlying mechanisms were analyzed. Wistar-Kyoto (WKY) rats with normal blood pressure were used as the blank control group, and spontaneously hypertensive (SHR) rats were selected as the experimental animals. In addition to freely consuming the basal diet daily, based on 1-fold and 2-fold of the recommended daily salt intake of 5 g/d, the low-dose groups of low-sodium salt (composed of 75% NaCl and 25% KCl) and magnesium-containing compound seasonings (composed of 65% NaCl, 25% KCl, and 10% MgCl2·6H2O) were set at 0.083 g/kg, equivalent to the body weight of SHR rats, and the high-dose groups were set at 0.167 g/kg. For the positive control group using irbesartan tablets, the dosage was calculated according to the standard. The blank control group and the model control group were administered an equal volume of pure water. All groups were intragastrically dosed for 28 days. Subsequently, general clinical observations were carried out, and the blood pressure and heart rate of the rats were measured. Finally, statistical analysis was performed. The results indicated that none of the test substances had a significant impact on the general condition and body weights of SHR rats. Compared with the model control group, the low-dose group of magnesium-containing compound seasonings could significantly reduce systolic blood pressure in the third week, with an average decrease of 10.71% when compared with the model group in the same period. This effect was comparable to that of irbesartan tablets and superior to that of low-sodium salt at the same dose. By the end of the fourth-week experiment, the decreases in systolic blood pressure in the low-dose groups of magnesium-containing compound seasonings and low-sodium salt, compared with the model control group, reached up to 6.01% and 7.63%, respectively. There was no statistically significant difference in the effects of low-sodium salt and magnesium-containing compound seasonings on reducing diastolic blood pressure, mean arterial pressure, and heart rate (P > 0.05). In conclusion, both low-sodium salt and magnesium-containing compound seasonings are conducive to maintaining healthy blood pressure levels, with no distinct difference. They can both reduce systolic blood pressure, but neither has a significant effect on reducing diastolic blood pressure. Since magnesium-containing compound seasonings have a greater advantage in dietary sodium reduction when compared with low-sodium salt, they are worthy of being vigorously developed as a substitute for low-sodium salt that benefits the maintenance of healthy blood pressure levels in the future.